Isolation and Analysis of DNA Fragment of Genes Related to Kopyor Trait in Coconut Plant - S, Sukendah; Volkaert, Hugo; S, Sudarsono (Indonesian Journal of Biotechnology, 2009)
Kopyor coconut is a natural mutant that has abnormal endosperm development. For the first time several genes that were suspected to be related to kopyor trait were identified based on the chemical compounds of the endosperm that different from that of normal coconut. Sucrose synthase (SUS), Stearoyl acyl carrier protein desaturase (SACPD), and Absicid acid insensitive (ABI) genes were isolated and analyzed. Four DNA fragments with length of 746, 738, 780, and 687 bp (CnSus1A, CnSus1B, CnSus2A, and CnSus2B) were obtained from SUS gene. Sequence analysis at DNA and amino acid level showed that CnSus1A, CnSus1B, CnSus2A, and CnSus2B were classified into monocot SUS group with nongrass SUS type. Isolation of SACPD gene resulted in one DNA fragment with DNA length of 716 bp. CnSacpd shared a high homology with SACPD gene of oil palm and soybean. Isolation of ABI gene resulted in two DNA fragments, CnAbi3A and CnAbi3B, with DNA length of 760 and 728 bp, respectively. CnAbi3A and CnAbi3B showed a high homology with ABI3 gene of several plants. All DNA fragment obtained from SUS, SACPD, ABI genes were used as templates to design spesific markers for each corresponding gene. There were 7 specific primer sets designed, i.e., CnSUS1A, CnSUS1B, CnSUS2A, CnSUS2B, CnSACPD, CnABI3A, and CnABI3B.<